2015
DOI: 10.1007/s13555-015-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Emergence of Novel Therapeutics in Advanced Malignant Melanoma

Abstract: For decades, no cancer therapy had been shown to improve average survival in metastatic melanoma. Two critical events have occurred, the discovery of melanoma driver mutation subsets and the discovery of immune checkpoint inhibitors, which have allowed for the development of modern, effective therapies. These findings have facilitated a rapid emergence of novel therapeutics for the disease with multiple FDA approvals in the last several years. The drugs vemurafenib, trametinib, and dabrafenib, which inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…Checkpoint inhibitors are effective in the treatment of metastatic melanoma, with approval of the first antibodies in the U.S. in 2011 [ 1 ]. Ipilimumab, the anti-CTLA4 antibody, demonstrated an increased overall survival [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Checkpoint inhibitors are effective in the treatment of metastatic melanoma, with approval of the first antibodies in the U.S. in 2011 [ 1 ]. Ipilimumab, the anti-CTLA4 antibody, demonstrated an increased overall survival [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The outcome of patients with late-stage disease has improved considerably with the development of targeted therapy and immunotherapy agents including vemurafenib, dabrafenib, ipilimumab, nivolumab and pembrolizumab. [2][3][4] This improvement is expected to continue over the coming years. Novel immunotherapy agents may have better outcomes in patients with low-volume asymptomatic disease, making early detection of metastases important.…”
Section: Conflicts Of Interest: None Declaredmentioning
confidence: 98%
“…It has been observed that treating the basic inflammatory condition improved insulin sensitivity and subsequently the glycaemic control. [3][4][5] Nevertheless, the nature of glycaemic control in diabetic patients with concomitant psoriasis has been given little attention to date.…”
Section: Conflicts Of Interest: None Declaredmentioning
confidence: 99%
“…More patients with cancer are living longer due in part to advances in molecular biology and the development of novel-targeted therapies [ 1 ]. There is growing recognition that assessment of the quality of this extended survival is important, namely how broader aspects of patients’ lives are managed and affected.…”
Section: Introductionmentioning
confidence: 99%